Modal Sosial dan Pengembangan Profesi Berkelanjutan Guru Sosiologi di Boyolali dan Surakarta - Yosafat Hermawan Trinugraha; Abdul Rahman; Septina Galih Pudyastuti; Saifuddin Zuhri; Okta Hadi Nurcahyono; Nurhadi Nurhadi (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This study aims to identify and analyze the forms and potential of social capital possessed by sociology teachers in Boyolali Regency and Surakarta City. It also seeks to explore the actors and institutions involved in developing teachers’ social capital and examines how sociology teachers utilize and enhance their social capital for professional development. Data were collected through interviews and document studies using a descriptive qualitative approach. The findings reveal that sociology teachers in Surakarta City have diverse perspectives on sustainable professional development. However, they agree that it must be continuously nurtured and advanced. Regarding social networks, a key component of social capital, teachers have leveraged existing networks such as Subject Teacher Deliberations at city/regency and provincial levels. Additionally, some teachers have sought alternative networks, including international NGOs and writing communities, to support their professional growth. The study highlights the need for teachers to embrace alternative networks beyond traditional ones to expand their social capital and sustain their professional development effectively.